Where Is The Cheese? Synthesizing a Giant Literature on Causes and Consequences of Financial Sector Development - Selşah Paşalı, Selahattin (World Bank, Washington, DC, 2014)
A likely image of the current state of the literature on financial sector development is that of a Swiss cheese with many holes inside important areas of knowledge. The aim of this synthesis paper is to map the current knowledge and ignorance (i.e., holes) in the literature by providing a narrative for the empirical findings of a comprehensive literature review concerning the quantitative effects of financial development on economic growth and employment, and various determinants of financial sector development. The literature was restricted mostly to high-quality academic research that focuses on developing countries over the period 1960-2012. Because of data constraints, this review also includes cross-country analyses, in which developed and developing countries are considered together. The main findings include (i) a positive relationship between financial development and economic growth and employment, subject to a number of qualifications; (ii) a complicated relationship of regulations and supervision to financial sector development; and (iii) a positive relationship between an enabling institutional environment and financial sector development. This review also identifies some missing avenues in the literature and provides a number of suggestions for future work.